The Image of Political Discourse in Peruvian University Research: A Look through Its Theses - Turpo Gebera, Osbaldo; Martinez Puma, Elena; Tomaylla Quispe, Ignacio; Chirinos Tovar, Karina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The study employs a documentary review methodology to analyse the evolution of political discourse in postgraduate theses (master's and doctoral) defended in Peruvian universities. The review encompasses 24 theses. The study identifies trends and discursive representations related to the subjectivities, mediations, and manipulations of the involved actors. The results reveal a growing academic interest, concentrated in universities in the capital, and highlight the ideological complexity of the discourses, ranging from the defence of the economic model to the redefinition of the social contract. The investigative focus reveals the creation of imaginary realities to strengthen political figures and highlights the influence of the media on public perception.